Identifying and evaluating sustainability risks in circular business models: Empirical insights from the heavy equipment manufacturing industry - Yudi Syahrullah; Udisubakti Ciptomulyono; Ratna Sari Dewi (Universitas Muhammadiyah Magelang, 2026)
Circular business models (CBMs) are increasingly being adopted in heavy equipment manufacturing to extend the value of end-of-life (EoL) components through recovery practices. However, existing sustainability risk assessments largely rely on generic literature-based risk lists without verifying their contextual relevance to specific industries. This study addresses this gap by systematically exploring and validating sustainability risks that are specifically relevant to circular manufacturing in the heavy equipment sector. An initial set of 32 sustainability risks was identified through literature review and cross-industry exploration. These sustainability risks were then evaluated using the Fuzzy Delphi Method (FDM) to manage uncertainty and establish expert consensus on their relevance to circular business models in the heavy equipment manufacturing sector. Based on the consensus criteria (d < 0.2; agreement ≥ 75%), 14 risks were validated as contextually relevant. The findings reveal that the most critical risks are concentrated in key circular activities, particularly those related to occupational health and safety hazards in EoL component recovery, and inaccurate or insufficient evaluation of the quality of components or products to be recovered. The main contribution of this study lies in moving beyond generic sustainability risk identification toward context-specific validation of sustainability risks in circular manufacturing. By filtering and confirming sustainability risks that truly reflect industrial realities, the results provide a robust foundation for targeted sustainability risk assessment and mitigation. Practically, the validated sustainability risk set provides decision-makers and engineers with a more precise basis for prioritizing sustainability risks and enhancing the resilience of circular manufacturing systems.